The effectiveness of DD Mag'z (digestive disease magazine) with google meet synchronously to improve digestive health literacy - Ilham - Nurseha; Mieke Miarsyah; Rizhal Hendi Ristanto (Indonesian Journal of Biology Education, 2021)
Digestive health literacy is important for students to be able to determine their diet, choose healthy foods, prevent and know the actions that need to be taken in treating diseases or disorders of the digestive system, and even promoting healthy living behaviors to others. This study aims to develop instructional designs to improve student health literacy with the ADDIE model. The development carried out consisted of developing lesson plans, assessment instruments, and learning media DD Mag'z (digestive disease magazine). Based on the results of the analysis, the learning design was determined using DD Mag'z and Google Meet synchronously. Expert validation was carried out assessing three aspects consisting of the feasibility of media, content, and language. The results of the validation of the developed media obtained an average value of 3.58 and were included in the very valid category so that it was suitable to be used as an alternative learning media on the concept of the digestive system. Measurement of the improvement of students' digestive health literacy skills used a dual choice instrument as a pre-test and post-test. The effectiveness analysis used a one group pre-test post-test design and obtained data that were not normally distributed. The Wilcoxon test results showed an effect of the synchronous use of DD Mag'z media with Google Meet on students' health literacy. While the results of the effectiveness test using N-Gain showed an average value of 0.41 so that the effectiveness of the instructional design developed was moderate.